HYPERINSULINAEMIC HYPOGLYCAEMIA (HH) IN A MOSAIC TURNER SYNDROME TODDLER - FN, Zainuddin; M, Noordin; MA, Basri; SC, Chee; NS, Mohd Nor (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Hyperinsulinaemic hypoglycaemia(HH) is a rare but important cause of hypoglycaemia, especially in the newborn. Early identification and diligent management of these patients is vital to prevent neurological insult. We report an interesting case of a toddler with mosaic Turner Syndrome(TS) with HH, responsive to diazoxide treatment. RESULTS A 25-month-old girl was born term via Emergency Lower Segment Caesarean Section(EMLSCS) for fetal distress with a birth weight 2.75 kg. No significant antenatal issue noted. Her Apgar score were 9 and 10 at 1 and 5 minutes of life. However, she was admitted to Neonatal Intensive Care Unit(NICU) at 7 hours of life, following symptomatic hypoglycaemia, whereby her capillary blood glucose recorded was 0.9 mmol/L. She required initial D10% bolus 3 mls/kg and subsequently required maintenance dextrose intravenous infusion with highest Glucose Delivery Rate of 14.4mg/kg/hour to maintain normoglycaemia. Despite that, there were recurrent episodes of hypoglycaemia. She was started on IVI Glucagon on day 9 of life, with highest concentration of 20 mcg/kg/hour. Oral Diazoxide was started at day 17 of life following measurable insulin level during critical sampling when the child developed significant hypoglycaemia. Currently, she is still on oral Diazoxide 2.6 mg/kg/day with no hypoglycaemic episodes. Karyotype was sent in view of subtle features of TS which includes high arch palate and hypertelorism and revealed Mosaic TS with 46X, +mar (18)/45,X(12). CONCLUSION In summary, we report an interesting association of mosaic Turner Syndrome with Hyperinsulinaemic Hypo-glycaemia. The recognition of hypoglycaemia in this group of patients is vital, as untreated hypoglycaemia may lead to irreversible brain damage. The mechanism leading to hyperinsulinism in this condition is not well established to the best of our knowledge and warrants further research.